2017
DOI: 10.15255/cabeq.2016.833
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Properties of Immobilized Biocatalysts with Lipase Activity Produced by Yarrowia lipolytica in Batch Culture

Abstract: Three kinds of matrices (calcium alginate, gelatin, and PVA) were employed as supports to immobilize lipases from Y. lipolytica KKP 379 via physical adsorption. The stability of biocatalysts (free and immobilized) was evaluated by measuring the enzyme activity before and after treatment with the method based on the hydrolysis of p-nitrophenyl laurate. Two fractions of enzymes were immobilized: cell-bound (yeast biomass) and extracellular (supernatant). The yield of immobilization and catalytic properties of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Fickers et al [28] detected LIP7 and LIP8 genes from Y. lipolytica which encode two cell-bound lipases that are easily released by washing the cells with phosphate buffer. Since in the present study the cells are treated with ultrasonic waves to obtain the biocatalyst, the lipase that remains attached to cell debris should be strongly bounded, in contrast to the one attached to biomass as reported by Stolarzewicz et al [27] and therefore, LipImDebri might be a more stable biocatalyst.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Fickers et al [28] detected LIP7 and LIP8 genes from Y. lipolytica which encode two cell-bound lipases that are easily released by washing the cells with phosphate buffer. Since in the present study the cells are treated with ultrasonic waves to obtain the biocatalyst, the lipase that remains attached to cell debris should be strongly bounded, in contrast to the one attached to biomass as reported by Stolarzewicz et al [27] and therefore, LipImDebri might be a more stable biocatalyst.…”
Section: Resultsmentioning
confidence: 61%
“…Finally, after ten recycles, the relative activity was marginally 10% of the initial value. Stolarzewicz et al [27] observed more than 70% decrease in lipase activity in the second use of Y. lipolytica biomass with bound lipase, immobilized on alginate beads. Fickers et al [28] detected LIP7 and LIP8 genes from Y. lipolytica which encode two cell-bound lipases that are easily released by washing the cells with phosphate buffer.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for this is the leakage of the enzyme from the structure of the microcapsules to the reaction medium. Stolarzewicz et al [ 29 ] reported leakage of cell-bond lipase immobilized in alginate, but in the second cycle only 25% of activity was detected. These microcapsules were tested in a leaking buffer for protein and lipase activity and no protein was detected and just a non-significant activity was determined ( Table A2 , Appendix A ).…”
Section: Resultsmentioning
confidence: 99%
“…Lipase production was carried out in a New Brunswick Microferm MF-114 reactor with an effective volume of 3 L, with 2 mL of antifoam and 3 L of the crude OFR culture medium consisting of residual frying oil, 2.5% ( v / v ), peptone, 6.4 g/L and yeast extract 10 g/L [ 29 ]. The fermentation was conducted with mechanical agitation (3 Rushton-type stirrers), stirring speed of 650 rpm, aeration rate of 1.5 L·min −1 , and temperature of 28 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, enzymatic synthesis methods open new ways of producing valuable products under mild conditions in contrast to traditional chemical methods (Pradima et al 2017). (Stolarzewicz et al 2017). Yeast biomass was then separated by centrifugation (10°C, 8 000 rpm, 10 min), washed twice by 0.9% sodium chloride solution and freeze-dried for 24 h using Christ Gamma 1-16 laboratory freeze dryer (Germany).…”
Section: Introductionmentioning
confidence: 99%